A genealogy of post-truth: philosophy, affects, technology - Arias-Maldonado, Manuel Jesús (My University, 2018)
How to make sense of both post-truth and post-factualism? As the erosion of truth seems to be on the rise in contemporary societies, apparently threatening the deliberative function assigned to their public spheres and thus the very health of democratic systems, it has become a necessity to deal with these closely related concepts. Do they refer to the same socio-political phenomenon? Where do they come from? What factors may explain their current diffusion? This paper will provide a genealogy for post-truth and post-factualism, carefully distinguishing between them before sheding light on their common roots -a conceptual task that should facilitate a careful assessment of their importance and thus help to devise strategies to counter their negative effects. To such end, the paper will explore three different dimensions of post-truth: (i) the philosophical, which relates to the long theoretical discussion about the possibility of truth, the conclusion of which is largely sceptical about a strong positicion on universally recognizable truths; (ii) the affective, which takes into account the insights provided by the contemporary literature on emotions, so that those features of human subjectivity that restrain a deliberative engagement with truth-seeking processes, or distort the individual perception of arguments and data that contradicts our belief, are identified; and (iii) the technological, which takes into account the social networks that largely organize public discussion nowadays and the way in which they strenghten both post-truth and post-factual tendencies. All in all, the gradual convergence of these three currents explains the rise of post-truth democracies.
Keywords: Ciencias políticas - Congresos; Post-verdad; Democracia; Digitalización; Posmodernismo; Afectos